ggggggggggg
in Algebra 1 Answers by

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:
To avoid this verification in future, please log in or register.

1 Answer

-⅕(2y-5x)=4, so 2y-5x=-20.  Multiply through by 3: 6y-15x=-60.

3y=1-8x, so 3y+8x=1. Multiply through by 2: 6y+16x=2.

(6y+16x)-(6y-15x)=2-(-60)=62.

31x=62, x=62/31=2.

3y=1-8x=1-16=-15, so y=-15/3=-5.

SOLUTION: x=2, y=-5.

by Top Rated User (660k points)

Related questions

2 answers
asked Oct 2, 2015 in Other Math Topics by Mathical Level 10 User (57.4k points) | 109 views
1 answer
asked Oct 2, 2015 in Other Math Topics by Mathical Level 10 User (57.4k points) | 124 views
3 answers
asked Oct 11, 2012 in Calculus Answers by anonymous | 1.1k views
2 answers
asked May 19, 2012 in Calculus Answers by anonymous | 145 views
1 answer
1 answer
asked May 29, 2013 in Algebra 1 Answers by anonymous | 136 views
0 answers
asked Jan 15, 2013 in Algebra 1 Answers by anonymous | 98 views
Welcome to MathHomeworkAnswers.org, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
83,158 questions
87,989 answers
1,978 comments
4,883 users